Efficacy and Safety of Lenacapavir for HIV Pre-Exposure Prophylaxis (Prep): A Systematic Review - Putu Ngurah Pradnya Wibawa; Ni Putu Lia Juliantini; Ni Luh Putu Serly Ekayanti (CV. Publikasi Indonesia, 2026)
Lenacapavir, an antiretroviral agent, is a candidate for HIV prophylaxis, distinguished by its long-acting formulation, which facilitates biannual administration for preventive care. The objective of this investigation is to assess the efficacy and safety profile of Lenacapavir, drawing upon the findings of extant research. This scoping review analyzed articles published between march 2016 and march 2026 from PubMed, ScienceDirect, and OpenAlex. The inclusion criteria comprised English-language cohort studies, case-control studies, and cross-sectional studies examining the association between NAFLD and the risk of CKD. Fifteen articles were selected following a rigorous screening process. Lenacapavir is a highly effective HIV preventive drug that can reduce the risk of HIV transmission among various populations, including pregnant women, homosexual and heterosexual individuals, and others. The reported side effects are generally mild and not severe. Lenacapavir signifies a significant advancement in the realm of HIV prevention, especially for individuals at elevated risk who encounter challenges with consistent daily medication adherence. The effective global deployment of this intervention hinges on several critical factors: guaranteeing equitable accessibility, ensuring affordability within low- and middle-income nations, and upholding rigorous HIV testing protocols to mitigate the potential for viral resistance.